2001
DOI: 10.1016/s0168-1591(00)00186-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of perches and nestboxes by laying hens in relation to social status, based on examination of consistency of ranking orders and frequency of interaction

Abstract: Four groups of 15-19 adult ISA Brown hens were studied in pens to assess the relationship between social status and use of perches and nestboxes. This was to test the hypothesis that subordinate hens use these resources more by day, for avoiding dominants, but that dominants use perches more at night, for roosting. The experiment consisted of a 5-week pre-treatment period, when no perches were present, and a 4-week treatment period, when each group was tested with different perch treatments (No, Low, Medium, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 26 publications
2
49
0
Order By: Relevance
“…Chickens may also use elevated structures to escape from other hens (Cordiner and Savory, 2001). These authors sequentially provided small groups of 20 adult hens with no perches or combinations of perches in low (17.5 cm above ground), medium (highest perch 35 cm above ground) or high (highest perch 70 cm above ground) configurations.…”
Section: Motivation To Perch During the Daymentioning
confidence: 99%
See 1 more Smart Citation
“…Chickens may also use elevated structures to escape from other hens (Cordiner and Savory, 2001). These authors sequentially provided small groups of 20 adult hens with no perches or combinations of perches in low (17.5 cm above ground), medium (highest perch 35 cm above ground) or high (highest perch 70 cm above ground) configurations.…”
Section: Motivation To Perch During the Daymentioning
confidence: 99%
“…Because of the rather low number of papers, this descriptive analysis was not able to account for lack of independence, differences in sample size and other important sources of heterogeneity. Three papers (Struelens et al, 2008b;Tuyttens et al, 2013;Chen et al, 2014) referred to cage systems and the three others (Cordiner and Savory, 2001;Newberry et al, 2001;Brendler et al, 2014) referred to non-cage systems.…”
Section: Available Datamentioning
confidence: 99%
“…The flow chart documents the number of studies identified by the search, the number Data were available from 10 studies to assess the outcomes of interest. The majority of studies (9) assessed perch use (Cordiner and Savory, 2001;Newberry et al, 2001;Riber et al, 2007;Brugesch et al, 2012;Eusebio-Balcazar et al, 2013;Tuyttens et al, 2013;Brendler et al, 2014;Chen et al, 2014). Only 1 assessed keel bone issues (Wilkins et al, 2011).…”
Section: Study Selection (Prisma Item 17)mentioning
confidence: 99%
“…This is an overly simplistic representation of the data, as it ignores many aspects that should be considered in a more though metaanalysis i.e., the group sizes to weight the analysis, the inclusion of covariates (including cage height, housing system), differences in metrics (some studies have average proportions of birds with groups o birds as the unit of concern and others have the bird as the unit of concern), differences in central tendency measure (some use median others mean), clustering by study (i.e., some studies contribute multiple data points) and differences in day and night time usage. Data from the only some studies could be extracted and included in the figures (Cordiner and Savory, 2001;Newberry et al, 2001;Tuyttens et al, 2013;Brendler et al, 2014;Chen et al, 2014). These data of course have issues associated with lack of independence between observations, for example, the study by (Tuyttens et al, 2013) includes observations on the same animals over time.…”
Section: Additional Analyses (Prisma Item 23)mentioning
confidence: 99%
See 1 more Smart Citation